Postoperative Rotator Cuff - Adler, Ronald S. (Seminars in Musculoskeletal Radiology, 2013)
This article provides a brief overview of the current state of ultrasound (US) imaging of rotator cuff repairs with emphasis on current morphological assessment and development of newer techniques in which US may play an important role in assessing healing response. Emphasis is on the supraspinatus tendon inasmuch as it is the most commonly affected tendon in rotator cuff disease. Assessment of the tendon repair following joint replacement is also commented on in which the standard anterior approach may be associated with dehiscence of the subscapularis tendon.
Keywords: shoulder; rotator cuff; ultrasound; repair; postoperative